Long-term humoral and cellular immune responses elicited by a heterologous Plasmodium vivax apical membrane antigen 1 protein prime/adenovirus boost immunization protocol. - Bouillet, L; Dias, M; Dorigo, N; Moura, A; Russell, B; Nosten, F; Renia, L; Braga, E; Gazzinelli, RT; Rodrigues, M; Soares, I; Bruna-Romero, O (2011)
Apical membrane antigen 1 (AMA-1) is an invasion-related Plasmodium antigen that is expressed during both intracellular and extracellular asexual stages of the parasite's life cycle, making it an ideal target for induction of humoral and cellular immune responses that can protect against malaria. We show here that when it is administered as a recombinant protein (P) in Montanide ISA720 adjuvant, followed by a recombinant human type 5 adenovirus (Ad), intense and long-lasting Plasmodium vivax AMA-1-specific antibody responses (including both IgG1 and IgG2a), as well as proliferative memory T cell responses, can be detected in immunized mice. Memory T cells displayed both central (CD44(hi) CD62L(hi)) and effector (CD44(hi) CD62L(lo)) phenotypes, with the central memory phenotype prevailing (56% of AMA-1-specific proliferating cells). Considering the main traits of the memory immune responses induced against AMA-1, this particular sequence of immunogens (P followed by Ad), but no others (Ad/Ad, Ad/P, or P/P), displayed an optimal synergistic effect. These results give further support to the need for preclinical studies of P. vivax vaccine candidate AMA-1 administered in prime/boost protocols that include recombinant proteins and adenoviral vectors.